Effect of using medical cannabis clinic services in palliative care patients at MaeOn Hospital, MaeOn District, Chiang Mai Province - Singjai, Sommit (Journal of Nakornping Hospital, 2024)
Objective: To study effect of using medical cannabis in palliative care patients at MaeOn hospital MaeOn district ChiangMai province. Methodology: This was a quasi-experimental study with a non-random, purposive sampling method. The sample consisted of 36 cancer patients in palliative care who received treatment at Mae On Hospital, Mae On District, Chiang Mai Province, from October 3, 2022, to June 30, 2023. The participants were divided into an experimental group, which received treatment with a cannabis-containing formula at the medical cannabis clinic, and a control group, which received treatment with a conventional medicine formula. Data collection tools included a palliative care patient information record and the Edmonton Symptom Assessment System (ESAS) for quality of life assessment. Data were analzed using descriptive statistics and comparisons between groups were made using the Mann-Whitney U test, and Wilcoxon Signed Ranks Test. Results: The study results showed that in the experimental group of 18 participants, 44% were male, with an average age of 65.78 ± 10.63 years and an average cancer duration of 2.44 ± 1.72 years. In the control group, also with 18 participants, 50% were male, with an average age of 63.28 ± 12.85 years and an average cancer duration of 1.94 ± 1.39 years. After the experiment, the average quality of life score in the control group was 16.39 ± 6.32 points, compared to 10.67 ± 4.60 points in the experimental group, with a statistically significant difference (p=0.006). Additionally, the difference in average quality of life scores before and after the experiment was 1.00 ± 2.14 points in the control group and 7.83 ± 4.09 points in the experimental group, also showing a statistically significant difference (p<0.001). Conclusion: Medical cannabis can improve quality of life in palliative care. Therefore, this is another an alternative treatment for palliative care patients.